TELAAH IMPLEMENTASI KURIKULUM MERDEKA MELALUI METODE EVALUASI - Ridwan, M; Damayanti, Marshela Tri Desta; Diansah, M. May (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The Independent Curriculum is the latest breakthrough in the pillars of education that is expected to have a positive impact on education in Indonesia. In the implementation of the independent curriculum, there are many achievements and obstacles that can be used as evaluation materials for curriculum implementers, namely principals, teachers, and education parliamentarians. At various levels of education, the implementation of the independent curriculum has various challenges and obstacles, one of which is the lack of incentive training for teachers in implementing the independent curriculum in several educational institutions. The evaluation is in the form of government policy efforts to provide equality of support provided in the form of essence and material so that a comprehensive understanding is achieved for curriculum implementers in administration and implementation of curriculum implementation. In an effort to write this article, we as authors use the library research method, namely research conducted through the exploration of several information in the form of journals, articles and books related to the discussion, we as authors hope that this written work in the form of an article can help academics in expanding their horizons of knowledge and strengthening information that is relevant to the current curriculum situation. ABSTRAKKurikulum Merdeka merupakan trobosan terbaru dalam pilar pendidikan yang diharapkan mampu memberikan dampak positif bagi pendidikan di indonesia, didalam implementasi kurikulum merdeka banyak sekali pencapaian dan kendala yang dapat dijadikan sebagai bahan evaluasi bagi para pelaksana kurikulum yaitu kepala sekolah, guru, dan parlementer pendidikan. Diberbagai jenjang pendidikan implementasi kurikulum merdeka memiliki beragam tantangan dan kendala, salah satunya adalah kurangnya pelatihan yang insentif terhadap guru didalam penerapan kurikulum merdeka dibeberapa institusi pendidikan. Evaluasinya berupa upaya kebijakan pemerintah untuk memberikan pemerataan terhadap support yang diberikan berupa esensi dan material sehingga tercapai pemahaman yang komperehensif terhadap para pelaksana kurikulum dalam administrasi dan pelaksanaannya terhadap implementasi kurikulum. Dalam upaya penulisan artikel ini, kami sebagai penulis menggukan metode library research, yaitu berupa riset yang dilakukan melalui ekploasasi beberapa informasi berupa jurnal, artikel dan buku-buku terkait pembahasan, kami sebagai penulis mengharapkan karya tulis berupa artikel ini dapat membantu para akademisi dalam memperluas cakrawala pengetahuan dan penguatan terhadap suatu informasi yang relevan dengan situasi kurikulum saat ini.